Improvement of drug delivery micro-circulatory system with a novel pattern of CuO-Cu/blood hybrid nanofluid flow towards a porous stretching sheet. Issue 11 (25th June 2019) - Dinarvand, Saeed; Nademi Rostami, Mohammadreza; Dinarvand, Rassoul; Pop, Ioan
Abstract : Purpose: This paper aims to simulate the steady laminar mixed convection incompressible viscous and electrically conducting hybrid nanofluid (CuO-Cu/blood) flow near the plane stagnation-point over a horizontal porous stretching sheet along with an external magnetic field and induced magnetic field effects that can be applicable in the biomedical fields like the flow dynamics of the micro-circulatory system and especially in drug delivery. Design/methodology/approach: The basic partial differential equations (PDEs) are altered to a set of dimensionless ordinary differential equations (ODEs) with the help of suitable similarity variables which are then solved numerically using bvp4c scheme from MATLAB. Inasmuch as validation results have shown a good agreement with previous reports, the present novel mass-based algorithm can be used in this problem with great confidence. Governing parameters are both nanoparticle masses, base fluid mass, empirical shape factor of both nanoparticles, suction/injection parameter, magnetic parameter, reciprocal magnetic Prandtl number, Prandtl number, heat source parameter, mixed convection parameter, permeability parameter and frequency ratio. The effect of these parameters on the flow and heat transfer characteristics of the problem is discussed in detail. Findings: It is shown that the use of CuO and Cu hybrid nanoparticles can reduce the hemodynamics effect of the capillary relative to pure blood case. Moreover, as the imposed magnetic field enhances, the velocity of the blood decreases. Besides, when the blade shapes for both nanoparticles are taken into account, the local heat transfer rate is maximum that is also compatible with experimental observations. Originality/value: An innovative mass-based model of CuO-Cu/blood hybrid nanofluid has been applied. The novel attitude to one-phase hybrid nanofluid model corresponds to considering nanoparticles mass as well as base fluid mass to computing the solid equivalent volume fraction, the solid equivalent density and also solid equivalent specific heat.